Multinational firms and the quest for global talent: Employing (skilled) foreign workers at home and abroad - Belderbos, René; Leten, Bart; Nguyen, Ngoc Hân; Vancauteren, Mark (Journal of International Business Studies, 2025)
Multinational firms can access global talent in two ways: by employing migrants in their home country, or by employing foreign workers in their overseas affiliates. Taking a knowledge-based perspective, we conceptualize these employment decisions as simultaneous and subject to management coordination. Substitution effects are greater when there is a larger wage cost differential between home and host countries, leading to a cost-reduction motivation for foreign expansion and the offshoring of employment. Substitution also occurs when R&D intensive firms employ highly skilled and internationally mobile foreign workers and employ these where the worker’s knowledge and skills can be most productively put to use. In contrast, a complementary relationship occurs when the migrant country exhibits a high contextual distance with the home country of the firm, leading to knowledge (diversity) benefits of migrant employment at home when expanding abroad. Analyzing employee–employer and foreign affiliate data for multinational firms in the Netherlands (2008–2016) and estimating simultaneous equation models, we find support for these hypotheses. Our findings suggest that policies that restrict immigration may have a negative impact on the competitiveness of home-country multinational firms by limiting their ability to engage in value enhancing coordination of domestic and foreign employment growth.